Effect of dehydration of Syrah grape berries on the aging potential of fortified sweet wines in Ningxia of China - Xiaoxi Zhang; Kaixian Wang; Qun Wang; Zhenan Shi; Hélder Oliveira; Nuno Mateus; Fuliang Han (Food Chemistry: X)
Many of wines from western China suffer from the short lifespan of aging. This study was conducted to investigate the effects of grape dehydration on aging potential of fortified sweet wines. Compared with the control wine (CK), dehydration significantly raised the sugar, organic acids and acetic esters content of G20 and G40 wines (made by 20 % and 40 % weight loss grapes). Dehydration also enhanced the stability of anthocyanins and the color of wines. After 24 months of aging, G20 had the highest monomeric anthocyanin content, and the variations of a⁎, b⁎ and H⁎ab values were lowest in G40. Furthermore, dehydrated samples presented better aging stability with the improved sensory characteristics such as stronger black fruit fragrance, fuller body and richer aftertaste. In general, Syrah fortified sweet wine provides a new option for high quality wines with stable color, concentrated aroma, rich taste, and high aging potential in Ningxia of China.